2013
DOI: 10.1071/an13037
|View full text |Cite
|
Sign up to set email alerts
|

Grazing systems and worm control in sheep: a long-term case study involving three management systems with analysis of factors influencing faecal worm egg count

Abstract: Abstract. Managing infections of sheep with gastrointestinal nematode parasites (worms) and problems of resistance to anthelmintic treatments continue to be major challenges for graziers on the Northern Tablelands of New South Wales, Australia. The whole-farmlet study of grazing enterprises undertaken by the Cicerone Project tested the broad hypotheses that compared with typical management (farmlet B), internal parasites can be more effectively managed with improved nutrition (farmlet A) or by intensive rotati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…Over all years, the average length of grazing periods, at the level of paddocks and sub-paddocks, on farmlets A, B and C was 45, 75 and 11 days, respectively, while the length of rest periods was 64, 66 and 98 days, respectively (Walkden-Brown et al 2013). As explained in detail in a related paper by Scott et al (2013b), stocking rates were adjusted after management took into account assessments of pastures and stock condition and thereby determined the numbers of ewes to be joined on each farmlet in April-May of each year.…”
Section: Livestock and Pasture Management Decisionsmentioning
confidence: 99%
“…Over all years, the average length of grazing periods, at the level of paddocks and sub-paddocks, on farmlets A, B and C was 45, 75 and 11 days, respectively, while the length of rest periods was 64, 66 and 98 days, respectively (Walkden-Brown et al 2013). As explained in detail in a related paper by Scott et al (2013b), stocking rates were adjusted after management took into account assessments of pastures and stock condition and thereby determined the numbers of ewes to be joined on each farmlet in April-May of each year.…”
Section: Livestock and Pasture Management Decisionsmentioning
confidence: 99%
“…Overall, gastrointestinal nematodosis (GIN), as indicated by faecal worm egg count, was significantly reduced on farmlet C compared with the other two farmlets (Colvin et al 2008;Walkden-Brown et al 2013). The greatest impact was seen on Haemonchus contortus, with a lesser impact on the other major nematode species (Trichostrongylus spp.…”
Section: Parasitesmentioning
confidence: 80%
“…* The changes in fleece characteristics between farmlets did not result in substantial differences in fleece values per head but, because of differences in stocking rate, wool production and thus wool value per hectare differed substantially (Cottle et al 2013). * Short grazing and long rest periods resulted in a decline in the numbers of Barber's pole worms in sheep leading to less reliance on anthelmintic drenches (Colvin et al 2008;Walkden-Brown et al 2013). * The detailed financial records which were kept of all input costs, including labour, and income allowed computation of gross margin and cash flow budgets as well as financial risk for each farmlet, which were then scaled up to allow comparisons relevant to commercial-scale whole farms .…”
Section: Some Results From the Farmlet Experiments Includementioning
confidence: 99%
“…Whereas the studies into intestinal worm burdens showed great benefits from intensive rotational grazing (Colvin et al 2008;Walkden-Brown et al 2013), it was also obvious that excessively long rest periods resulted in lower individual animal performance, which required the adjustment of graze and rest periods to overcome this disadvantage .…”
Section: Reflections From the Livestock Producersmentioning
confidence: 99%
See 1 more Smart Citation